Food security and sustainable agricultural management with small producers families (Revista Sistemas de Producción Agroecológicos, 2018)
This work was carried out in Restrepo, Meta, Colombia, in which participated families who had been displaced of their farms because of the armed conflict. For the development of the project the pedagogical and technical components oriented to the social projection were used, with didactic materials such as: study guides, folding, audiovisual aids, visits to the premises of some members of the community and field practices. The objective of the work was to put into practice the knowledge related to food security and environmental education, themes in which the community had already been trained, and has allowed them to improve their quality of life. A survey was applied to families in order to know aspects related to the benefits offered by the food safety training program, for this case, community education was used as an updating and training mechanism, which was carried out for the purpose of informing and inquiring into the community about how effective was the inclusion process through the information of agricultural units and food security. Once the diagnostic phase was analyzed, a planning was structured with the community of activities such as: schedule of visits and technical advice, design of strategies and pedagogical tools, selection of the themes inherent to the management of appropriate technologies for vegetable, fruit, corn and sugarcane crops; and planning of extension activities such as demonstrations of method, field days and tours. The families were provided with supplies and materials necessary to develop the food security project and technical advisory activities. According to the agreed schedule, accompaniment and counseling visits were made to the families who gave continuity to their project following a sustainable management of family agricultural units. The 86% of the producers indicated that they had developed some of the food security projects: 29% have established family orchards, 7% poultry only, 7% poultry and fish farming, 7% poultry, orchard and fish farming, and 43% have implemented poultry and vegetable orchards. The educational strategies used in the process of social projection were exhibitions, discussions, workshops, field days, practical theoretical classes and demonstration of methods; which were considered relevant by part of the community, who stated that these activities facilitated learning because simple language was used.
Keywords: pedagogical project; family farming; educational strategies